2021
DOI: 10.1111/jgs.17599
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, sadness, and feelings of social disconnection in older adults during the COVID‐19 pandemic

Abstract: Background Public health measures to control the COVID‐19 pandemic have led to feelings of loneliness among older adults, which, prior to COVID, has been associated with subsequent morbidity and mortality. We sought to identify differences in feelings of loneliness, sadness, and social disconnection early in the pandemic across racial groups, and possible mitigating factors. Methods We performed a cross‐sectional analysis using the weighted nationally‐representative Medicare Current Beneficiaries Survey COVID‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 45 publications
(125 reference statements)
1
68
0
Order By: Relevance
“…While there is mixed evidence for whether occurrence of loneliness changed during the COVID-19 pandemic, with some literature demonstrating an increase ( Ausín et al, 2021 ; Holaday et al, 2022 ; Elran-Barak & Mozeikov, 2020 ) and some demonstrating no change ( Luchetti et al, 2020 ; McGinty, Presskreischer, Han, & Barry, 2020 ; Latikka, Koivula, Oksa, Savela, & Oksanen, 2022 ), examinations have shown that certain groups, including women, those living alone, and those who are younger, were all at higher risk of increased loneliness during COVID-19 ( Bu, Steptoe, & Fancourt, 2020 ; Li & Wang, 2020 ) as well as increased risk of psychiatric disorder ( Li & Wang, 2020 ). Importantly, work has also revealed that loneliness was linked to greater increases in psychological distress and anxiety during the pandemic, especially in these groups ( Latikka et al, 2022 ; McDonald et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is mixed evidence for whether occurrence of loneliness changed during the COVID-19 pandemic, with some literature demonstrating an increase ( Ausín et al, 2021 ; Holaday et al, 2022 ; Elran-Barak & Mozeikov, 2020 ) and some demonstrating no change ( Luchetti et al, 2020 ; McGinty, Presskreischer, Han, & Barry, 2020 ; Latikka, Koivula, Oksa, Savela, & Oksanen, 2022 ), examinations have shown that certain groups, including women, those living alone, and those who are younger, were all at higher risk of increased loneliness during COVID-19 ( Bu, Steptoe, & Fancourt, 2020 ; Li & Wang, 2020 ) as well as increased risk of psychiatric disorder ( Li & Wang, 2020 ). Importantly, work has also revealed that loneliness was linked to greater increases in psychological distress and anxiety during the pandemic, especially in these groups ( Latikka et al, 2022 ; McDonald et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, delayed medical care utilization and discontinued care-more pronounced during the COVID-19-are expected to adversely affect older adults' health status in the future (60). Here, telemedicine is a promising tool with great potential in reducing unmet healthcare needs (61) and its uptake in some countries after the outbreak was exceptional (33).…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is common, particularly during the COVID‐19 pandemic, prompting many clinicians and researchers to assess for loneliness. 1 , 2 , 3 However, the best approach for screening is unclear. One option is a single question directly asking about loneliness (“how often are you lonely?”).…”
Section: Introductionmentioning
confidence: 99%